Type I interferon gene signature test–low and –high patients with systemic lupus erythematosus have distinct gene expression signatures. (November 2019) - Brohawn, PZ; Streicher, K; Higgs, B W; Morehouse, C; Liu, H; Illei, G; Ranade, K
Objectives: Type I interferon (IFN) is implicated in systemic lupus erythematosus (SLE) pathogenesis. We aimed to identify type I IFN signaling-dependent and -independent molecular pathways in a large population of patients with SLE. Methods: Baseline blood samples from adult patients with moderate to severe SLE from two Phase IIb studies (NCT01438489, n = 265; NCT01283139, n = 416) were profiled using whole transcriptome array analyses. Type I IFN gene signature (IFNGS) test status (high or low) was determined using a validated qualitative polymerase chain reaction–based test. IFN-type-specific signatures were developed by stimulating healthy blood with IFN-β, IFN-γ, IFN-λ, IFN-ω, or pooled IFN-α. These, and multiple literature-derived cell type and cytokine pathway signatures, were evaluated in individual and pooled study populations. A Fisher's exact test was used for associations, adjusted for false discovery rate. Results: Whole blood samples from IFNGS test–high patients were enriched versus IFNGS test–low patients for CD40L signaling ( Q < 0.001), CXC cytokine ( Q < 0.001), TLR8-mediated monocyte activation ( Q < 0.001), IgG ( Q < 0.001), major histocompatibility complex class I ( Q < 0.001), and plasma cell ( Q < 0.001) gene expression signatures. IFNGS test–low patients had significant enrichment of eosinophil ( Q < 0.001), IFN-γ-specific ( Q = 0.005), and T-cell or B-cell ( Q < 0.001) signatures. Similar enrichment profiles were demonstrated in patients with primary Sjögren's syndrome, systemic sclerosis, and dermatomyositis. Conclusions: IFNGS test–high patients overexpressed many gene signatures associated with SLE pathogenesis compared with IFNGS test–low patients, reflecting broad immune activation. These results provide new insights into the molecular heterogeneity underlying SLE pathogenesis, highlighting shared mechanisms beyond type I IFN, across several autoimmune diseases. Trial registration: Clinicaltrials.gov: NCT01438489 and NCT01283139.